Cumulus Cell Transcriptome after Cumulus-Oocyte Complex Exposure to Nanomolar Cadmium in an In Vitro Animal Model of Prepubertal and Adult Age - Nicola Antonio Martino; Ernesto Picardi; Elena Ciani; Anna Maria D’Erchia; Luisa Bogliolo; Federica Ariu; Antonella Mastrorocco; Letizia Temerario; Luigi Mansi; Valeria Palumbo; Graziano Pesole; Maria Elena Dell’Aquila (Biology, 2023)
Cadmium (Cd), a highly toxic pollutant, impairs oocyte fertilization, through oxidative damage on cumulus cells (CCs). This study analysed the transcriptomic profile of CCs of cumulus-oocyte complexes (COCs) from adult and prepubertal sheep, exposed to Cd nanomolar concentration during in vitro maturation. In both age-groups, CCs of matured oocytes underwent RNA-seq, data analysis and validation. Differentially expressed genes (DEGs) were identified in adult (n = 99 DEGs) and prepubertal (n = 18 DEGs) CCs upon Cd exposure. Transcriptomes of adult CCs clustered separately between Cd-exposed and control samples, whereas prepubertal ones did not as observed by Principal Component Analysis. The transcriptomic signature of Cd-induced CC toxicity was identified by gene annotation and literature search. Genes associated with previous studies on ovarian functions and/or Cd effects were confirmed and new genes were identified, thus implementing the knowledge on their involvement in such processes. Enrichment and validation analysis showed that, in adult CCs, Cd acted as endocrine disruptor on DEGs involved in hormone biosynthesis, cumulus expansion, regulation of cell signalling, growth and differentiation and oocyte maturation, whereas in prepubertal CCs, Cd affected DEGs involved in CC development and viability and CC-oocyte communications. In conclusion, these DEGs could be used as valuable non-invasive biomarkers for oocyte competence.